COVID-19 Grounded Aircraft - Parking and Storing - Francisco Serrano; Antonín Kazda (Communications - Scientific letters of the University of Zilina, 2021)
Air transport industry is one the many sectors significantly impacted by the COVID-19 pandemic. Travel restrictions and bans resulted in reduction in aircraft operation. Airlines have no option than to limit their services by grounding their fleet: as of April 2020, out of 22,000 passenger aircraft around the world, almost 14,400 were grounded [1]. Airport operators are trying to accommodate most of the grounded aircraft by utilizing their main operational space as aprons, taxiways and runways. The limited space at airports often means that aircraft have to be parked in non-standard positions, which may affect the airport daily operations. While planning aircraft parking, safety is the top priority. The effect of long-term load was not considered in the pavement design and could result in increased pavement maintenance requirements. Airport operators must also reflect aircraft maintenance needs in terms of engines, hydraulics, braking system, cabin interior and others.